Application of Hydride Process in Achieving Equimolar TiNbZrHfTa BCC Refractory High Entropy Alloy - Bhupendra Sharma; Kentaro Nagano; Kuldeep Kumar Saxena; Hiroshi Fujiwara; Kei Ameyama (Crystals, 2020)
For the first time, an equiatomic refractory high entropy alloy (RHEA) TiNbZrHfTa compact with a single-phase body-centered cubic (BCC) structure was fabricated via a titanium hydride (TiH2) assisted powder metallurgy approach. The constituent pure Ti, Zr, Nb, Hf, and Ta powders were mechanically alloyed (MA) with titanium hydride (TiH2) powder. The resultant MA powder was dehydrogenated at 1073 K for 3.6 ks and subsequently sintered through spark plasma sintering (SPS). Additionally, TiNbZrHfTa counterparts were prepared from pure elements without MA with TiH2. It was observed that the compact prepared from pure powders had a chemically heterogeneous microstructure with hexagonal close packed (HCP) and dual BCC phases. On the other hand, despite containing many constituents, the compact fabricated at 1473 K for 3.6 ks via the hydride approach had a single-phase BCC structure. The Vickers microhardness of the TiNbZrHfTa alloy prepared via the hydride process was Hv 520 (±30). The exceptional microhardness of the alloy is greater than any individual constituent, suggesting the operation of a simple solid-solution-like strengthening mechanism and/or precipitation hardening. In addition, the heat treatments were also carried out to analyze the phase stability of TiNbZrHfTa prepared via the hydride process. The results highlight the substantial changes in the phase as a function of temperature and/or time.